Migracje i transfery kapitału społecznego - Isański, Jakub (Wydawnictwo Naukowe UAM, 2015)
This book deals with the processes of contemporary Polish migration and presents changes that occur in social life in relation to these processes. It should be emphasized that these changes occur among migrants themselves and also in the places in which they settle and which they leave. This is facilitated by maintaining contacts and social networks, paying regular visits and sending remittances. The book consists of four chapters. The first chapter presents the history of sociological reflection on migration and its social consequences; particu-lar emphasis is placed on the role of social remittances. The second and third chapters are devoted to selected topics in the theory of social capital and present an attempt at linking this theory to the phenomenon of migration and social remittances. The last, fourth, chapter de-scribes the phenomenon of contemporary migration based on field research that was carried out among Polish migrants both in Poland and abroad in 2011–2013.

Książka przedstawia zagadnienie przemian społecznych związanych ze współczesnymi polskimi migracjami zarobkowymi. Koncepcja transferów społecznych lokuje zachodzące zmiany zarówno wśród migrantów, jak i w obszarach ich pochodzenia. Określanie siebie przez odniesienie do innych ludzi i miejsc, w których przebywamy, w epoce migracji zyskuje nowe znaczenia. Przed laty oraz współcześnie, migracjom często przypisuje się prorozwojowy charakter obejmujący nie tylko samych migrantów, ale i inne osoby z ich gospodarstwa domowego, również kraje przyjmujące, a nawet kraje, z których wyjeżdżają. W monografii podjęto próbę omówienia wybranych wątków teoretycznych, dotyczących kapitału społecznego, aktualności i pojemności, ale też kilku poważnych słabości tej teorii. Drugim zasadniczym celem pracy jest przedstawienie współczesnych polskich migracji międzynarodowych i ich wpływu na zmiany życia społecznego ze szczególnym uwzględnieniem nowego podejścia teoretycznego: koncepcji transferów społecznych.
Migration and the Transfer of Social Capital
Keywords: kapitał społeczny; migracje zarobkowe; transfery kapitału; transfery pieniężne